The Role of Volunteerism in Achieving Sustainable Development: A field study on teachers of the khebrat Program 2 in the Kingdom of Saudi Arabia - Alhummiani, Mazen Saud Mohammed; Shuaibi, Faisal Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at explaining the role of volunteerism in achieving sustainable development, and that is by highlighting the importance of volunteerism and the role of the volunteer in seeking to improve conditions (environmental, social, economic, national) for all members of society and the country as a whole. The researcher used the descriptive analytical method in conducting this study since he used a questionnaire to collect primary data from the study’s society, which consisted of all Khebrat 2 teachers in the Kingdom of Saudi Arabia, the sample of the study covered 322 teacher, and then the questionnaires were unloaded and analyzed using SPSS statistical software and adequate statistical tests. The study found many results, the most prominent of them were: The existence of a statistically significant correlation between (motives for volunteering, obstacles to volunteering, impact of volunteer) and sustainable development in its various dimensions (environmental, social, economic, and national), where the coefficient of correlation between volunteer work with its various elements and sustainable development in its various dimensions reached a value of (0.211). In light of the results of the study, the researcher proposes several recommendations as follows: Work to provide a clear system and wise management that contributes to the organization of the work of each volunteer within the school. Increasing the number of seminars and meetings held by the school administration with community members to increase awareness of the environment and the risks it faces. Enhancing the efforts made by the school administration with the efforts of officials in the community to present initiatives that contribute to the development of the local economy.
Keywords: volunteer work; sustainable development; experience program; Ministry of Education